Answer :

(a) sin (x + y) sin(x – y)

= (sin x.cos y + sin y.cos x)( sin x.cos y - sin y.cos x)

= sin2x cos2y+ sin y.cos x. sin x.cos y- sin x.cos y sin y.cos x- sin2y cos2x

= sin2x cos2y- sin2y cos2x

= sin2x(1- sin2y)- sin2y(1- sin2x)

= sin2x- sin2x sin2y- sin2y+ sin2x sin2y

= sin2x – sin2y

(a) matches with (iv)

(b) cos(x + y) cos(x – y)

= (cos x.cos y−sin x.sin y)( cos x.cosy+sin x.siny)

= (cos2x cos2y+ cos x.cos y sin x.siny- sin x.sin y cos x.cosy- sin2x sin2y)

= cos2x cos2y- sin2x sin2y

= cos2x(1- sin2y)-(1- cos2x) sin2y

= cos2x- cos2x sin2y- sin2y+ cos2x sin2y

= cos2x – sin2y

(b) matches with (i)


(c) matches with (ii)


(d) matches with (iii)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

True and False<brMathematics - Exemplar

Find the values oRD Sharma - Mathematics

Prove that :
RD Sharma - Mathematics

The value of cos<Mathematics - Exemplar

The value of sin Mathematics - Exemplar

cos 2θ cos 2<spanMathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar